A Novel dPdI feedback based control scheme using GWO tuned PID controller for efficient MPPT of PEM fuel cell. (October 2019) - Rana, K.P.S.; Kumar, Vineet; Sehgal, Nitish; George, Sunitha
Abstract: At any operating condition, there is only one maximum power point (MPP) where proton exchange membrane fuel cell (PEMFC) is desired to operate. For this task, a maximum power point tracking (MPPT) controller is generally employed. In this paper, a novel and simple d P d I feedback based control scheme, employing Grey wolf optimizer (GWO) tuned PID controller, is proposed for efficient MPPT of PEMFC. The performance of the GWO tuned PID is controller is compared with two classical techniques namely, P&O and INC and for a fair comparison of choice of optimization method, the former was also compared with PSO tuned PID Performance of the proposed MPPT scheme is assessed under varying operating conditions using root mean square power ripple and maximum power ripple as performance metrics. Presented simulation results clearly indicate superiority of the proposed technique. Therefore, it is concluded that d P d I feedback scheme based GWO tuned PID controller is a more effective MPPT technique for PEMFC. Graphical abstract: Highlights: A novel d P d I feedback based scheme is investigated for MPPT of PEMFC system. A unique set-point d P d I = 0, is proposed for attaining MPP in PEMFC. The used set-point is universal as it is independent of operating conditions. A GWO tuned d P d I feedback based PID controller is investigated.